Determinants of policy and uptake of national vaccine programs for pregnant women: results of mixed method study from Spain, Italy, and India - Lois Privor-Dumm (Human Vaccines & Immunotherapeutics, 2021)
An important strategy for addressing maternal and newborn risks of disease is through vaccinating pregnant women. We conducted a mixed-methods study including a narrative literature review of drivers of maternal vaccination and key informant interviews in Spain, Italy, and India to characterize different approaches to national maternal immunization programs. Fifty-nine respondents participated in the study conducted between November 2018 and January 2019. Policies in Spain and Italy both reflect a life-course approach to vaccination, but recommendations and how they ensure uptake differs. Italy was focused on tracking of progress and mandates to ensure compliance in all regions, while Spain, an early adopter, relied more on advocacy and building provider acceptance. India includes Td in their national program, but the political will and advocacy for other vaccines are not seen. Needs for improving rates of maternal vaccination include education of health-care providers and pregnant women, use of central registries to track progress, stronger global guidance for use of vaccines, and engagement of champions, particularly obstetrician-gynecologists (ob-gyns). Health security concerns can also be leveraged to build political priority and needed platforms to detect disease and deliver vaccines in some countries. Understanding what drives a country’s maternal immunization program decisions and the success of implementation is useful in designing strategies to share best practices and guide support to strengthen platforms for maternal vaccination.